Radioprotective properties of flurbiprofen - Hofer, M; Pospísil, M; Pipalová, I (Folia biologica, 1996)
Repeated administration of flurbiprofen, an inhibitor of prostaglandin synthesis (IPS), was found to enhance haemopoiesis in mice exposed to a sublethal dose of fractionated gamma-irradiation (5 x 3 Gy, intervals between fractions 24 h). In lethally irradiated animals (5 x 3 Gy and an additional "top-up" dose of 3.5 Gy), a significantly better survival was found in mice given flurbiprofen than in control animals receiving saline. The latter result is a new positive phenomenon not observed in earlier experiments with other IPS. The findings suggest a possibility to extend the radiation dose range, in which the administration of IPS leads to radioprotective effects, also to higher, lethal radiation doses, by administering flurbiprofen instead of previously studied IPS indomethacin or diclofenac.
Keywords: Flurbiprofen; flurbiprofen; Lymphocytes; myši inbrední C57BL; mužské pohlaví; antagonisté prostaglandinu; Granulocytes; lymfocyty; Mice; záření gama; myši inbrední CBA; granulocyty; slezina; ženské pohlaví; zvířata; Prostaglandin Antagonists; myši; Mice, Inbred CBA; Female; Spleen; Mice, Inbred C57BL; Gamma Rays; Male; Animals